Pharyngocutaneous fistula as an alternative access route for inserting a percutaneous endoscopic gastrostomy tube in head and neck cancer patients - Di Palma, Louise Deluiz Verdolin; Mello, Gustavo Francisco de Souza e; Granados, Cindy Lis; Glória, Ricardo Dardengo; Dalbem, Caroline Sauter; Cruz, Rolantre Lopes da; Ayres, Ana Carolina Maron; Lisboa, Renata Sofia Camara; Pelosi, Alexandre Dias; Ferreira, Maria Aparecida; Mansur, Gilberto Reynaldo; Silva, Simone Guaraldi da; Ribeiro, Theresa Christina Damian; Dias, Fernando Luiz (Endoscopy International Open, 2017)
Background and study aims Performing a percutaneous endoscopic gastrostomy (PEG) in head and neck cancer (HNC) patients can be challenging because of the presence of trismus, pharyngeal obstruction by tumor, and pharyngoesophageal strictures or fistula. Pharyngocutaneous fistula (PCF) is a major postoperative concern in patients submitted to total laryngectomy (TL). In the medical literature to date, the cervical fistula has been used as an access to PEG in only four reports. The aim of this study was to evaluate the safety of cervical fistula for insertion of a PEG tube.Patients and methods Retrospective study at a single tertiary referral center, regarding the technical feasibility, safety and outcomes of a PEG tube introduced by a cervical fistula in HNC patients with obstructive lesions of the oropharynx. Results The procedure was technically successful in all 21 patients. A PEG tube was used for a minimum of 1 month and a maximum of 120 months. Twelve patients died while using the PEG tube, 8 had it taken out because it was no longer needed, and only 1 had the tube still in use. Adverse events occurred in 8 patients: granuloma (19 %), dermatitis (9.5 %), accidental late removal of the tube (9.5 %), periprocedural gastric wall hematoma (9.5 %), peristomal wound infection (4.7 %), buried bumper syndrome (4.7 %), and traumatic gastric ulcer (4.7 %).Conclusion A postoperative cervical fistula can successfully work as a reliable and safe access for a PEG tube procedure in HNC patients, avoiding unnecessary surgery and reducing costs.